Stand-alone student planner system - Then, Nyet Kim (Universiti Malaysia Sarawak, UNIMAS, 2005)
In this Final Year Project, the target user of Stand-alone Student Planner System will be focus on secondary school students. The programming language used for implement the Studen talone Student Planner System is Visual Basic 6.0 and Microsoft Access 2000 is used to implement the database. The implementation of Stand-alone Student Planner System is based on user’s requirements. Thus the users can easily adapt to all of the provided features that help users to manage their time and work easily and efficiently. Even though faced problem that are inevitable during implementation, the objectives of the system is achieved. Comments and recommendation is used to produce a more efficient and effectiveness Standalone Student Planner System.